Democracy, Public Expenditures, and the Poor : Understanding Political Incentives for Providing Public Services - Keefer, Philip; Khemani, Stuti (Oxford University Press on behalf of the World Bank, 2013)
The incentives of politicians to provide broad public goods and reduce poverty vary across countries. Even in democracies, politicians often have incentives to divert resources to political rents and private transfers that benefit a few citizens at the expense of many. These distortions can be traced to imperfections in political markets that are greater in some countries than in others. This article reviews the theory and evidence on the impact on political incentives of incomplete information for voters, the lack of credibility of political promises, and social polarization. The analysis has implications for policy and for reforms to improve public goods provision and reduce poverty.